China's public health policies in response to COVID-19: from an “authoritarian” perspective - Gao, Jinghua; Zhang, Pengfei (Frontiers in Public Health, 2021)
Background: China is generally regarded internationally as an “authoritarian” state. Traditional definitions have assigned many negative connotations surrounding the term of authoritarian. We realize that it might not be considered value-neutral in other countries. But authoritarian in the Chinese context emphasizes more on centralized decision making, collectivism, coordinating all activities of the nation, and public support, which is considered a value-neutral term. Therefore, it is adopted in this paper. We would like to clarify this. Authoritarian governance is considered an important mechanism for developing China's economy and solving social problems. The COVID-19 crisis is no exception. Most of the current research on crisis management and government crises focuses on advanced, democratic countries. However, the consequences of crisis management by authoritarian governments have not been fully appreciated. Although prior research has addressed authoritarian initiatives to manage crises in China, authoritarian interventions have rarely been theorized in public health emergencies.Methods: Based on a literature review and theoretical analysis, we use a descriptive and qualitative approach to assess public health policies and mechanisms from an authoritarian perspective in China. In light of the key events and intervention measures of China's government in response to COVID-19, the strategic practices of the Communist Party of China (CPC) to construct, embody, or set political goals through authoritarian intervention in public health crisis management are discussed.Results: China's government responded to the COVID-19 pandemic with a comprehensive authoritarian intervention, notably by establishing a top-down leadership mechanism, implementing a resolute lockdown, rapidly establishing square cabin hospitals, enhancing cooperation between different government departments, mobilizing a wide range of volunteer resources, enforcing the use of health codes, imposing mandatory quarantine on those returning from abroad, and implementing city-wide nucleic acid testing. These measures ensured that China was able to contain the outbreak quickly and reflect on the unique role of the Chinese authoritarian system in responding to public health crises.Conclusions: Our paper contributes to expanding the existing understanding of the relationship between crisis management and authoritarian system. China's response to COVID-19 exemplifies the unique strengths of authoritarian institutions in public health crisis management, which is a helpful and practical tool to further enhance the CPC's political legitimacy. As a socialist model of crisis management with Chinese characteristics, it may offer desirable experiences and lessons for other countries still ravaged by the epidemic.